Comparison of AC/A Ratio in True and Simulated Divergence Excess Exotropia: http://doi.org/10.36351/pjo.v37i2.1192 - Sagheer, Sana; Haider, Muhammad Ali; Bukhari, Attaullah Shah; Sattar, Uzma; Ahmed, Iftikhar (Pakistan Journal of Ophthalmology, 2021)
Purpose: To compare the accommodation convergence per accommodation ratio (AC/A) in true and simulated divergence excess exotropia. Study Design: Comparative cross sectional study. Place and Duration of Study: Department of ophthalmology, Punjab Rangers teaching hospital, Lahore, from July 2019 to December 2019. Methods: The study included 20 patients each of intermittent exotropia (XT) true and simulated divergence excess exotropia (XT).All the subjects underwent complete orthoptic assessmentthat included AC/A ratio calculation through heterophoria method after monocular occlusion. Results: The Results showed that patients with true divergence excess exotropia have a high AC/A ratio as compared to patients with simulated divergence excess exotropia who have a normal AC/A ratio. 57% patients showed true divergence excess exotropia with high AC/A ratio while 43% had divergence excess with normal AC/A ratio. Conclusion: The response of AC/A was found to be higher in patients with true divergence excess exotropia after monocular occlusion. Key Words: Intermittent exotropia, True simulated divergence excess exotropia, simulated divergence excess exotropia.